Childbearing and the Changing Nature of Parenthood : the Contexts, Actors, and Experiences of Having Children. - Pisco Costa, Rosalina (Contemporary Perspectives in Family Research Ser., 2019)
Around the globe, the very conceptualization of family is associated with the relationship between a parent and a child. The birth of a child represents both the end of one experience, and the beginning of another.